Progress and Challenges in Research on Cognitive Architectures - Langley, Pat (Proceedings of the AAAI Conference on Artificial Intelligence, 2017)
Research on cognitive architectures attempts to develop unified theories of the mind. This paradigm incorporates many ideas from other parts of AI, but it differs enough in its aims and methods that it merits separate treatment. In this paper, we review the notion of cognitive architectures and some recurring themes in their study. Next we examine the substantial progress made by the subfield over the past 40 years, after which we turn to some topics that have received little attention and that pose challenges for the research community.